2021
DOI: 10.3389/fimmu.2021.632353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in KIR/HLA-C Genes Are Associated With the Susceptibility to HCV Infection in a High-Risk Chinese Population

Abstract: BackgroundKIR/HLA-C signaling pathway influences the innate immune response which is the first defense to hepatitis C virus (HCV) infection. The aim of this study was to determine the association between the genetic polymorphisms of KIR/HLA-C genes and the outcomes of HCV infection in a high-risk Chinese population.MethodsIn this case-control study, four single nucleotide polymorphisms (SNPs) of KIR/HLA-C genes (KIR2DS4/KIR2DS1/KIR2DL1 rs35440472, HLA-C rs2308557, HLA-C rs1130838, and HLA-C rs2524094) were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, further validation of this observation in an independent cohort with various HCV-genotypes is recommended. The KIR diversity between different populations reported by other groups [13,14] is not a likely explanation as there was no statistically significant difference between the frequency of KIR allelotype in the non-cancer HCV patients in the Italian cohort and the Egyptian cohort (25.6% vs. 27%, p = 0.8843).…”
Section: Discussionmentioning
confidence: 79%
“…However, further validation of this observation in an independent cohort with various HCV-genotypes is recommended. The KIR diversity between different populations reported by other groups [13,14] is not a likely explanation as there was no statistically significant difference between the frequency of KIR allelotype in the non-cancer HCV patients in the Italian cohort and the Egyptian cohort (25.6% vs. 27%, p = 0.8843).…”
Section: Discussionmentioning
confidence: 79%
“…Takeji et al found that KIR3DL1 + HLA‐Bw4 are associated with HCC development in HCV cirrhosis, and Zhengang et al found that KIR2DL5A−/2DL5B + associated with HCV spontaneous clearance 22,23 . Recently, single nucleotide polymorphisms (SNPs) of KIR2DS4/KIR2DS1/KIR2DL1 and HLA‐C have been linked to an elevated vulnerability to HCV infection in our previous study 24 …”
Section: Introductionmentioning
confidence: 70%
“…[19][20][21] 22,23 Recently, single nucleotide polymorphisms (SNPs) of KIR2DS4/KIR2DS1/KIR2DL1 and HLA-C have been linked to an elevated vulnerability to HCV infection in our previous study. 24 KIR2DL4 is referred to as one of the "framework" genes, which was detected 100% in random populations. 25 Structured questionnaires designed by professionals were completed to collect subjects' information with demographic information, harmful behavior exposure, and clinical histories of HCV infection.…”
mentioning
confidence: 99%
“…Interestingly, NK-cell proteins with the highest donor-variations in the BL group can be functionally associated in a protein-protein-interaction network and enrich lysosomal and endosomal as well as HLA classes I and II components. HLA genotypes have been associated with viral load and more recently with susceptibilities in HCV risk groups and now may support the further classification of chronic HCV patients [96][97][98]. In this context, it is reasonable to speculate on the role of sex hormones and sex-specific cytokine levels to explain donor-variations in the NK-cell proteomes of female patients.…”
Section: Discussionmentioning
confidence: 99%